(untitled) (Jurnal Respirologi Indonesia, 2018)
Based on calculations of over one million people in the world weighing excessively or known as obesity with body mass index (IMT) 25 kg / m2 or more. Obesity is the cause of morbidity, as is the case in the population of the United States an estimated 400,000 deaths caused due to obesity. Obesity especially abdominal obesity is a significant risk factor for cardiovascular diseases, type 2 diabetes, rheumatoid arthritis and cancer. The relationship between obesity and chronic respiratory illness began to increase and began to be recognized. The World Health Organization (WHO) predicts about 10% of the global population will be obese by 2015. (J Respir Indo 2018; 38(2): 123-33)